Open questions on chemistry in the synthesis and characterization of superheavy elements - Patrick Steinegger (Nature Portfolio, 2021)
Superheavy elements are ideal for furthering our understanding of relativistic effects and how they affect physicochemical properties of heavy elements. In this comment, the author discusses the role of chemistry in the synthesis of new elements before addressing the future challenges concerning the chemical characterization of superheavy elements.